Digital Marketing Strategy for International Expansion: A Case Study of Doctor Helmet Medan - Rahmat Putra Ahmad Hasibuan; Nurfadhilah Ahmad Hasibuan (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the digital marketing strategy employed by Doctor Helmet Medan for expanding its presence in international markets. Using a detailed case study approach, the research examines how the company effectively leverages cultural understanding across various global regions to customize its products and tailor digital marketing campaigns to meet diverse consumer preferences. Data collection methods included observation of digital marketing activities, interviews with key management personnel, and content analysis of social media and e-commerce platforms utilized by Doctor Helmet. The findings highlight that product adaptation aligned with regional cultural preferences, integrated use of social media combined with paid advertising, and optimization of e-commerce platforms are essential factors driving successful penetration into international markets. Additionally, challenges such as intense global competition, varying regulatory environments, and logistical complexities were identified as significant barriers that require continuous strategic adaptation. This study offers valuable practical insights for MSMEs and medium-sized enterprises aiming to design and implement effective digital marketing strategies for sustainable international expansion.